Evasão universitária no Bacharelado Interdisciplinar em Ciência e Economia - Oliveira, Edna De (2016)
This work is a study on evasion in the Interdisciplinary Bachelor of Science and Economics (BICE) from the Federal University of Alfenas - UNIFAL - MG. In the current socio-economic context, facing the challenges posed to the university, historical features of exclusion and higher education gentrification in Brazil and social yearnings for its democratization, the research addresses the evasion as one of the major problems presented to this level of education in Brazil. The expansion policies implemented in higher education, from REUNI, and that led to the creation of interdisciplinary bachelors, has faced the problem of evasion. The abandonment of the course by the student represents a waste of public resources and huge educational and social losses that threaten the effectiveness of the policies of expansion and democratization of higher education and is presented as a problem for the public administration. From the contributions of many scholars, especially Tinto (1975, 1993), evasion is now considered an issue which is the institution’s responsibility and it requires an active approach to coping. The central objective of this study was to characterize the evasion in the BICE, from 2009 to 2015, and propose actions to minimize the problem. The specific goals include: to measure evasion in the BICE; to present traces of evaded student's profile; and to identify the internal and external aspects of the institution and the personal aspects that influenced the evasion, from the perception of the students who left the course. The quantitative and descriptive, documentary and empirical research, occurred through institutional data and questionnaire administered to dropouts, which have recognized some evasion features on the course. The data showed that from the 2042 freshmen, from 2009 to 2015, 545 (26.68%) had already evaded in March 2016, which represents a dropout rate higher than the evasion of the national average in classroom courses offered by the IFES, which is 17%. The survey also revealed that the problem occurs especially with students who are at the beginning of the course and have low efficiency. The evasion in the BICE was also influenced by multiple factors that are present at the intersection of internal perspectives to the IES, external to the IES and personal factors. Among the most mentioned factors, the evaded students highlighted the interest in another course, the difficulty of reconciling work and study, the disenchantment with the course and the difficulty of participating in the IES activities, and these were shown to be related to internal aspects of the course or IES. Thus, the research points to the need for various institutional actions from the follow-up and discussion of the problem to support activities for guidance and student learning.